PLANNING OF ESTUARY RESERVOIR AND TRANSVERSAL WATERWAY FROM CENGKARENG DRAIN RIVER, DKI JAKARTA - Surya Nusantara, Yoga
Jakarta - Banten - West Java is a densely populated metropolitan area. Water demand continues to increase along with the increase of population and activities carried out. The problems that occur in this region are the availability of land, floods, rob, and water demands that are often not met. As a result of these unmet water demands, there is exploitation of groundwater which caused land subsidence. One solution provided for the problems is to build estuary reservoirs. The estuary reservoirs are planned in Jakarta Bay. The estuary reservoirs are divided into four clean water reservoirs and four dirty water reservoirs equipped with transversal channels as flood control channels and long storages. Each reservoir has a water source that originates from the river which empties into the Jakarta Bay. One of them is Cengkareng Drain. Cengkareng Drain is a downstream of two main rivers, namely Angke River and Pesanggrahan River. Watershed area of the Cengkareng Drain River is ± 430 km2. Clean water reservoir volume is obtained using the Ripple Method and dirty water reservoir volume is obtained from three daily flood discharge with a 100-year return period. The volume of clean water reservoir and dirty water reservoir are ± 112 million m3 and ± 84 million m3 with 1104.92 Ha new potential area. Cengkareng Drain transversal waterway planned to use flood discharge at the 25-year return for the clean water reservoir and 100 years for the dirty water reservoir. Flood discharge is obtained using the HSS ITB-1 method with a value of 625.30 m3/second and 699.06 m3/second. With the existence of the estuary reservoir and the transversal waterways, it is expected to minimize flood and tidal hazards that might be happening and can accommodate excess water that occurs during the rainy season to meet water demands during the dry season.